Considerations and Challenges for Acute Inhalation Toxicity Testing and Classification of Zinc Sulphide Under REACH - Gustav Gerd Bruer; Noömi Lombaert; Arne Burzlaff; Christine Spirlet; Daria Gödecke; Mehmet Ramazanoglu; Otto Creutzenberg (Toxics)
Zinc sulphide is a widely used inorganic powder, and its production has reached quantities greater than 1000 t/year. Therefore, in accordance with OECD guideline 436, an acute inhalation test was implemented to provide more accurate data. This study is crucial for ensuring the safety of workers exposed to zinc sulphide dust and complying with regulatory requirements for REACH. Due to particle-specific properties, the maximum attainable concentration of zinc sulphide for an inhalation study was not certain. Two dry dispersion systems were used to aerosolize the zinc sulphide powder, and the generated aerosol was supplied to a nose-only inhalation exposure system. The results showed a maximum attainable concentration of 0.82 mg/L at an MMAD of 1.5 µm over a 4 h exposure. In the inhalation study, all six rats showed no specific symptoms and good health status and survived a post-exposure observation period of up to 14 days. From the results observed, the status of Not classified was derived according to CLP. Based on the experimental results, an LC50 was not determined but is considered to be higher than 0.82 mg/L (the maximum achievable aerosol concentration). These findings highlight the importance of documenting efforts to achieve aerosol conditions when concentrations required by OECD test guidelines cannot be reached.